2x2+5x+3 = (2x+3)(x+1) when factored
This expression cannot be factored.
If you mean (1+2x)2, that is already factored.
2x2 + 5x = x*(2x + 5)
(2x - 1)(x + 3)
It is (2x-5)(x-4) when factored
2x2+9x+9 = (2x+3)(x+3) when factored
2x2-9x+4 = (2x-1)(x-4) when factored
If you mean: 2x^2 +9x +7 then it is (2x+7)(x+1) when factored
(5x-9)(2x-1) when factored
6x2 + 5x - 6 is factored out to (2x + 3)(3x - 2).
x2+2x-120 = (x+12)(x-10) when factored
2x2+5x-3 = (2x-1)(x+3) when factored
2(x - 3)(x - 3)
2x2-1x-120 = (2x+15)(x-8) when factored
no posible answerImproved Answer:-2x2+x-3 = (2x+3(x-1) when factored
It can not be factored because its discriminant is less than zero
4x3+10x2-6x 2x(2x2+5x-3) 2x(2x-1)(x+3)
That can be factored to -((x + 5)(x - 3))
It is the same as: x^2 +2x +1 and it is (x+1)(x+1) when factored
Factor out a 22(X2 + X - 12)2(X - 3)(X + 4)===========
x2 - 2x = x(x - 2)
2x + 3 can be factored as follows: 2(x + 1.5)